ANALISIS HUBUNGAN TINGKAT PENGETAHUAN IBU DENGAN KEJADIAN STUNTING MENGGUNAKAN PENDEKATAN KUANTITATIF: STUDI LITERATUR REVIEW - Delima Delima; Firman Firman; Afdal Afdal (HUMAN CARE JOURNAL, 2023)
The incidence of stunting in Indonesia is in the high category (24.4 percent), even though the WHO's maximum limit for stunting in a country is 20 percent. In West Sumatra at the end of 2021 it is 23%. The purpose of this study was to analyze the relationship between the mother's level of knowledge and the incidence of stunting using a quantitative approach. This research method uses a literature review study using articles in electronic databases, namely Google Scholar, Research Gate, and PubMed/Medline based on PRISMA (Preferred Reporting Items for Systematic Review & Meta Analysis). The search was carried out using the keywords "stunting", "Knowledge of Mothers". The analysis was carried out from 10 relevant articles, it was found that most of the mothers' knowledge was lacking about stunting. The results of the analysis show that there is a relationship between mother's knowledge and the incidence of stunting. To prevent stunting, counseling and information services can be carried out, to help solve problems faced by mothers, especially preventing stunting in children, especially in the first 1000 days of life